An Integrated Approach to Strengthening Public Health System Resilience Against Environmental and Disaster-Related Threats: A Literature Review - Hely Hely; Murni Noviani; Balqis Nurmauli Damanik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to develop an integrated framework for strengthening public health system resilience in the face of increasing environmental and disaster-related threats. While research on environmental health risks, administrative health governance, and disaster preparedness has progressed independently, public health systems continue to suffer from fragmented strategies. This fragmentation weakens coordinated responses during crises such as climate-driven disasters, pandemics, or infrastructure failures. Therefore, this review aims to synthesize current approaches and propose a unified model for adaptive and sustainable health system resilience. Materials and methods. A structured literature review was conducted using the PRISMA methodology. A total of 36 peer-reviewed articles published between 2018 and 2025 were analyzed. Selected studies were categorized into four thematic areas: environmental health, health governance, disaster preparedness, and integrated resilience models. Quantitative frameworks such as Delphi–AHP and system dynamics were reviewed alongside qualitative governance and policy analyses. Results.The findings reveal significant gaps in current public health resilience strategies. Although predictive modeling and hospital safety protocols are widely discussed, their implementation is often localized and not mainstreamed into national health policies. Governance issues such as fragmented leadership, limited budgets, and lack of inter-agency coordination were consistently cited. Only a few studies presented cross-sectoral resilience models. Conclusions.A unified resilience framework is essential for modern health systems. It must combine environmental forecasting, flexible governance, community engagement, and disaster preparedness. The proposed model provides a foundation for future research and policy innovation aimed at achieving resilient, equitable, and proactive health systems.